Association between educational level and knowledge on transmission of hiv/aids in adolescent women in Peru-ENDES 2019: Asociación entre nivel educativo y conocimiento sobre transmisión de vih/sida en mujeres adolescentes de Perú-ENDES 2019 - Amado Cornejo, Nathalie (2021)
Introduction: Knowledge about the transmission of HIV in adolescent women is important due to the great risk of contracting said infection. Objective: To determine the association between the educational level and knowledge about the transmission of HIV in female adolescents according to the ENDES year 2019. Methods: Quantitative, observational, retrospective, cross-sectional and analytical study based on the public availability data of the ENDES 2019. Results: Of the 4 668 women in the age range of 15 to 19 years. 30.6% had adequate knowledge about HIV and 69.4% had inadequate knowledge. No association was found between educational level and level of knowledge about HIV transmission. In the multivariate analysis, regarding the wealth index, being non-poor compared to being in extreme poverty has a positive influence on adequate knowledge about HIV (OR: 1.25 95% CI: 1.14–1.38). Conclusion: Knowledge about HIV transmission in adolescent women in Peru is not adequate, no association was found between educational level and knowledge about HIV transmission, nor with place of residence; but if an association was found with the wealth index.